2016
DOI: 10.1038/srep37818
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and genetic diversity in Centaurea subsect. Phalolepis in Anatolia

Abstract: Mountains of Anatolia are one of the main Mediterranean biodiversity hotspots and their richness in endemic species amounts for 30% of the flora. Two main factors may account for this high diversity: the complex orography and its role as refugia during past glaciations. We have investigated seven narrow endemics of Centaurea subsection Phalolepis from Anatolia by means of microsatellites and ecological niche modelling (ENM), in order to analyse genetic polymorphisms and getting insights into their speciation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The high levels of historical gene flow detected in the present study are consistent with the low genetic differentiation observed between species (Table 2 and Supplementary Table 3), which are significant but much lower than those reported for both Greek, Italian, and Turkish Centaurea subsect. Phalolepis ( F ST = 0.243, 0.232, and 0.198, respectively; López-Vinyallonga et al, 2015; López-Pujol et al, 2016; Garcia-Jacas et al, 2019). Moreover, we have not detected isolation by distance (except among C. gadorensis populations of Sierra de Gádor), suggesting that the lineage distribution is the result of historical phylogeography.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The high levels of historical gene flow detected in the present study are consistent with the low genetic differentiation observed between species (Table 2 and Supplementary Table 3), which are significant but much lower than those reported for both Greek, Italian, and Turkish Centaurea subsect. Phalolepis ( F ST = 0.243, 0.232, and 0.198, respectively; López-Vinyallonga et al, 2015; López-Pujol et al, 2016; Garcia-Jacas et al, 2019). Moreover, we have not detected isolation by distance (except among C. gadorensis populations of Sierra de Gádor), suggesting that the lineage distribution is the result of historical phylogeography.…”
Section: Discussionmentioning
confidence: 97%
“…Similar levels of genetic variability were found in species of Centaurea subsect. Phalolepis using almost the same set of microsatellite loci (mean H E = 0.587 and 0.504 for the Greek and Anatolian taxa, respectively; López-Vinyallonga et al, 2015; López-Pujol et al, 2016). For narrow endemic plants, the expected levels of genetic diversity are low, but in the Mediterranean mountains the endemisms appear to harbor moderate to high levels (cf.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As ecological niche modelling may be problematic for cases with occurrence records < 25, we applied the methodological approach developed by Pearson et al (2007) to confirm an accurate predictive performance of models, as described in López-Pujol et al (2016). Selected layers were used to build the definitive SDM models for the present time.…”
Section: Species Distribution Modellingmentioning
confidence: 99%